Gendered Spheres of Learning and Household Decision-Making over Fertility - Ashraf, Nava; Bakhtin, Maxim; Field, Erica; Voena, Alessandra; Ziparo, Roberta (Review of Economic Studies, 2026)
While men and women make joint decisions about fertility, women give birth and are more likely to learn about a significant cost of childbearing—maternal health risk. Within couples in Zambia, men have systematically lower awareness of maternal risk factors and higher desire for children than their wives. We develop a model in which information asymmetries between partners over maternal health risk can persist in equilibrium due to strategic incentives and can generate disagreement over fertility that cannot be resolved with transfers. To study the effect of communication barriers on fertility, we design an experiment that varies whether the husband or the wife receives information about maternal health risk. One year after the intervention, men told about such risk exhibit significant gains in knowledge, report lower demand for children, and communicate this information to their wives, who also update their beliefs. Pregnancy falls significantly, while transfers remain unchanged relative to the control group. Meanwhile, when women are told about risk, they update their beliefs, but fail to transmit the information to their husbands, who do not change their demand for children. While pregnancy also falls among these couples, the decline is accompanied by a significant reduction in transfers and support to the wife. When childbearing costs, particularly those borne by one party, cannot be easily communicated within the household, targeting information can help overcome asymmetries and improve household decision-making.